Reluctant Celebrity Affect and Privilege in Contemporary Stardom - York, Lorraine (Springer International Publishing, 2018)
In this book, Lorraine York examines the figure of the celebrity who expresses discomfort with his or her intense condition of social visibility. Bringing together the fields of celebrity studies and what Ann Cvetkovich has called the "affective turn in cultural studies", York studies the mixed affect of reluctance, as it is performed by public figures in the entertainment industries. Setting aside the question of whether these performances are offered "in good faith" or not, York theorizes reluctance as the affective meeting ground of seemingly opposite emotions: disinclination and inclination. The figures under study in this book are John Cusack, Robert De Niro, and Daniel Craig-three white, straight, cis-gendered-male cinematic stars who have persistently and publicly expressed a feeling of reluctance about their celebrity. York examines how the performance of reluctance, which is generally admired in celebrities, builds up cultural prestige that can then be turned to other purposes. .